Using RNAi in the treatment of cardiovascular diseases - therapeutics based on siRNA overview - Rusinowska, Barbara (Journal of Education, Health and Sport, 2022)
RNA interference (RNAi) discovered in the 1990s by Fire and Mello plays a role in silencing gene function. One type of RNAi is siRNA, which is a double-stranded molecule of 20-25 base pairs. This molecule is made by cleaving double-stranded RNA by the enzyme Dicer. siRNA binds to the protein complex with ribonuclease activity - RISC (RNA-induced silencing complex). The resulting complex binds to the mRNA and cuts it into parts, which blocks the formation of the protein encoded by the mRNA. This property has been exploited in the production of siRNA-based drugs. However, the instability of siRNA molecules turned out to be difficult - the challenge was to properly modify the structure of siRNA in order to increase the stability and half-life and select the appropriate method of delivering the molecule to the body. Many siRNA-based drugs have already been developed, but most are in clinical trials. In this review, we present the role of RNA interference in therapeutics production and use of siRNA in cardiovascular diseases treatment.